2011
DOI: 10.1080/09540121.2010.507952
|View full text |Cite
|
Sign up to set email alerts
|

Employment status is associated with both physical and mental health quality of life in people living with HIV

Abstract: To evaluate the relationship between employment status and health-related quality of life (HRQOL) in HIV/AIDS. A total of 361 participants provided baseline data in the context of an ongoing cohort study examining the natural history of neurobehavioral functioning and its effects on HRQOL. We administered tests and collected laboratory data to determine demographic status, HIV disease markers, psychosocial symptom burden, neurocognitive function and HRQOL (MOS-HIV). We performed regression analyses to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
107
5
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(134 citation statements)
references
References 42 publications
20
107
5
2
Order By: Relevance
“…One study conducted in Canada indicates that the social inclusion of PLWHA, due to their participation in the job market, was associated with improved QoL for both men and women with HIV. Among men, job stability was associated with improved mental health, which indicates the benefits of la- bor for one's mental health (Rueda, Raboud, Mustard, Bayoumi, Lavis & Rourke, 2011). This study's results concerning clinical aspects indicate there is a clear relationship between the immunological conditions of PLWHA and depressive symptoms, as described in other studies (Kaharuza et al, 2006;Silveira, Motta, Spack, Araujo & Pupulin, 2007).…”
Section: Discussionsupporting
confidence: 66%
“…One study conducted in Canada indicates that the social inclusion of PLWHA, due to their participation in the job market, was associated with improved QoL for both men and women with HIV. Among men, job stability was associated with improved mental health, which indicates the benefits of la- bor for one's mental health (Rueda, Raboud, Mustard, Bayoumi, Lavis & Rourke, 2011). This study's results concerning clinical aspects indicate there is a clear relationship between the immunological conditions of PLWHA and depressive symptoms, as described in other studies (Kaharuza et al, 2006;Silveira, Motta, Spack, Araujo & Pupulin, 2007).…”
Section: Discussionsupporting
confidence: 66%
“…Nowadays, HIV infection represents living with a chronic disease, which opens space for non-pharmacological interventions like physical exercise 21 . Physical exercise enables to maintain functionality and improves quality of life 22,23 , as our study has demonstrated. Thus, maintenance of physical and functional aptitude has become one of the priority objectives in the treatment of patients living with HIV/AIDS, mainly those with a diagnosis of pronounced loss of muscle mass 24 .…”
Section: Discussionmentioning
confidence: 68%
“…[18] 46% [17] 5-30%, WHO [29] for HIV and 72% [19] 46-47.2% [20] for tuberculosis, the lower prevalence rates of psychiatric co-morbidity found in this study particularly for HIV could be a reflection of increased awareness, following concerted efforts and aggressive campaigns by both government and voluntary organizations, more access to existing medical care, articulated interventional measures by government, such as the anti-retroviral and anti-tuberculosis schemes, and sustained efforts aimed at reducing stigma and discrimination [14,77].…”
Section: Discussionmentioning
confidence: 99%
“…This often worsens the prognosis of these illnesses, due to inadequate management with eventual high mortality rates. Late recognition of psychiatric disorders in HIV and Tuberculosis patients is related, among others, with diminished coping capacity at diagnosis [73,106,117,118] failure at primary prevention, poor antiretroviral and antituberculosis adherence [67,[101][102][103][104] reduced quality of life [42][43][44][45][46][47][48][49][50] greater social and emotional burden, overall high healthcare costs, [77,78] and also higher mortality [54,57].…”
Section: Introductionmentioning
confidence: 99%